Impact of COVID-19 pandemic on cardiac, respiratory and mental health through collaboration with physician, psychologist, Nursing, Nutritional and Epidemiological specialist - Majed Ali D Al Homaidhy 7, Sara Hassan Albeladi 8, Nahlah Mubark Alotaibi 9, Naif Dawas Talaa Alharbi 10, Zahra Sadeq Alnasser11, Saeed Alwuayli Saeed Alshahrani 12., Ghalib Nasser Mobark Aldawsari 1, Saud Nahed Saud Aldawsari 2, Eisa Nazzal Ali Alatawi 3 , Tareq Soliman Nazzal Alatawi 4, Ashraf Mohamed Ibrahim ALjaber 5, Sulaiman Qasem Saleem Alatawi 6 (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The COVID-19 pandemic significantly changed the focus of healthcare Team. In susceptible patient populations, these modifications may have had an impact on respiratory, cardiac, and mental health. The long-term effects of COVID-19 are not as well understood, however they can include persistence, sequelae, and other medical issues that last weeks or months after the initial recovery. In particular, as health care providers struggle to combat COVID-19, we also need to determine how the pandemic has affected people's cardiac, respiratory, and mental health. In conclusion, extended COVID represents a multifaceted illness with prolonged and varied symptoms, necessitating individualized care and continuous assistance for individuals experiencing COVID-19 aftereffects. On the other hand, an effective interprofessional team is essential to a crisis response's effectiveness. Aim: The purpose of the current systematic review is to locate studies that examine and evaluate the consequences of COVID-19 pandemic on cardiac, respiratory and mental health through a collaboration with physician, psychologist, Nursing, Nutritional and Epidemiological specialist. Design: A systematic review was formed from 32 studies that were included. Conclusion The respiratory, cardiovascular, and neurological systems have been intimately associated with the COVID-19 pandemic since its inception. The COVID-19 sequelae are a developing issue in the post-epidemic era. In order to investigate and control the course of the anomalies in the respiratory, cardiac sequelae of COVID-19 and its effect on mental health, A clinical, Nursing, psychological, Nutritional, pandemic control features should be taken into consideration. Careful monitoring of the disease in survivors is necessary